2016
DOI: 10.3390/ijerph13101040
|View full text |Cite
|
Sign up to set email alerts
|

Is Pedometer-Determined Physical Activity Decreasing in Czech Adults? Findings from 2008 to 2013

Abstract: Objective measured trend data are important for public health practice. However, these data are rare for an adult population. Therefore, the aim of this study was to describe time trends in pedometer-determined physical activity of Czech adults (25–65 years) from 2008 to 2013. Participants were Czech national citizens whose physical activity was assessed objectively using a Yamax Digiwalker SW-700 pedometer (Yamax Corporation, Tokyo, Japan) for seven consecutive days in the period 2008 to 2013. The final sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In this study women took more steps than men. This is in line with studies from Sweden, but in the USA [8] and the Czech Republic [13] men have been found to be more active than women. However, there may be a natural explanation in the longer steps (10%) of men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study women took more steps than men. This is in line with studies from Sweden, but in the USA [8] and the Czech Republic [13] men have been found to be more active than women. However, there may be a natural explanation in the longer steps (10%) of men.…”
Section: Discussionsupporting
confidence: 91%
“…Associations of partnering transition and socioeconomic status with a four-year change in daily steps among Finnish adults divorce PA decreased among men [12]. However, there are no objectively measured study results on PA changes over several years in Finland and only a few studies in other countries address the issue [7,13]. Measuring PA objectively is important for determining the health benefits of different amounts and intensity of PA [14].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) is one of the main components of a healthy lifestyle [1]. In the Czech Republic, about one-third of adults have a physically inactive lifestyle [2,3]. Globally, an insufficient level of PA was found in 23.4% of adults in Central and Eastern Europe and 36.8% in high-income Western countries [4].…”
Section: Introductionmentioning
confidence: 99%
“…The three devices were the mechanical Yamax Digiwalker SW200, the piezoelectric cantilever accelerometer-based Omron HJ720ITC, and MEMs capacitive sensor-based ActiGraph monitors. A reason for selecting these three devices was that unlike various consumer-based devices that are currently available, these three brands of devices have significantly influenced the creation of commonly used step goals (e.g., 10,000 steps/day) [ 13 , 14 , 15 ] and/or have been widely used in both population-level studies (e.g., NHANES) [ 16 , 17 , 18 , 19 , 20 ] and in clinical trials [ 15 , 21 , 22 , 23 ]. However, these devices also use unknown proprietary strategies to define a step.…”
Section: Introductionmentioning
confidence: 99%